2019
DOI: 10.21608/epsj.2019.48311
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Reducing Crude Protein on Gimmizah Chickens Performance During Late Laying Period 1- Supplemented With Zinc and Vitamin D3

Abstract: This study was performed to investigate the influence of low crude protein diet (LCP, 13%) and different dietary levels of zinc with or without vitamin D3 on the productive and reproductive performance of Gimmizah chickens during the late laying period. A total number of 280 (245 hens + 35 cocks) Gimmizah chickens aged 52-week were individually weighed and randomly divided into seven treatment groups with five replicates for each during the experimental period (52-64 weeks of age). The birds of the first group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…There have been claims that camel milk has anti-allergic properties where allergies can be brought on by a variety of foods, particularly ruminant milk and milk products, and some severe food allergies can cause anaphylactic responses 78 . Moreover, Khazaei et al 47 and Abou-Shehema et al 79 reported the protective effect of silymarin on the livers of aflatoxicated quail and broilers, respectively, which appeared in a decrease in serum ALT and AST concentrations. Muhammad et al 80 achieved the same outcomes, reporting that silymarin supplementation increased the serum protein of broilers.…”
Section: Discussionmentioning
confidence: 99%
“…There have been claims that camel milk has anti-allergic properties where allergies can be brought on by a variety of foods, particularly ruminant milk and milk products, and some severe food allergies can cause anaphylactic responses 78 . Moreover, Khazaei et al 47 and Abou-Shehema et al 79 reported the protective effect of silymarin on the livers of aflatoxicated quail and broilers, respectively, which appeared in a decrease in serum ALT and AST concentrations. Muhammad et al 80 achieved the same outcomes, reporting that silymarin supplementation increased the serum protein of broilers.…”
Section: Discussionmentioning
confidence: 99%
“…Some key characteristics of silymarin contribute to its protective effects: (I) it sustains vascular fluidity and consistency in the availability of toxic compound damage (Yunus et al, 2011); (II) it inhibits the conversion of stellate enterocytes into fibroblasts, which results in the accumulation of collagen fibres and liver disease (Fraschini et al, 2002); and (III) it inhibits the production of free radicals, such as hydroxyl radicals (Miguez et al, 1994). Alanine aminotransferase (ALT), glutamic oxaloacetic transaminase (SGOT) and alkaline phosphatase were vastly enhanced in the bloodstream by diets adulterated with aflatoxin B1, but this increment was prevented by silymarin administration (Abou‐Shehema et al, 2016). To maintain proper fluidity, silymarin inhibits unusual changes in the components of lipids by acting directly on biological membranes (Muriel & Mourelle, 1990).…”
Section: Different Types Of Plant Extract As Pfasmentioning
confidence: 99%